The Effect of Using LKPD Based of Problem Based Learning Model on Improving the Ability of Students’ Mathematical Communication - Hany Zahira; Zulkarnain; Putri Yuanita (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2020)
This research aims to know the effect of using LKPD based of Problem Based Learning model in improving Mathematical Communication Ability of Grade VIII Students at Dwi Sejahtera Junior High School Pekanbaru. The type of this research was Quasi Experimental Research with pretest-posttest control group design. The population was all students of Dwi Sejahtera Junior High School Pekanbaru Academic Year 2019/2020. The samples selection was conducted by using random sampling technique. Based on the result of data analysis, obtained the average score of posttest in Experimental Class 90,87, and the average score of the Control Class is 48,67. It means the average of Experimental Class is higher than the Control Class. The difference test of both averages used t-test obtained significance (2-tailed) 0,000 < α = 0,05 which means the average of posttest score of students’ Mathematical Communication Ability who learn by using LKPD based of PBL is different from the average score of posttest of students’ Mathematical Communication Ability who learn by using scientific learning model. Thus, it can be concluded that there is effect of Problem Based Learning model on students’ Mathematics Communication Ability.